Targeting transcription factor STAT3 for cancer prevention and therapy. - Chai, E.; Shanmugam, M.; Arfuso, Frank; Dharmarajan, Arunasalam; Wang, C.; Kumar, A.; Samy, R.; Lim, L.; Wang, L.; Goh, B.; Ahn, K.; Hui, K.; et al. (2015)
Signal Transducers and Activators of Transcription (STATs) comprise an important class of transcription factors that have been implicated in a wide variety of essential cellular functions related to proliferation, survival, and angiogenesis. Among various STAT members, STAT3 is frequently overexpressed in tumor cells as well as tissue samples, and regulates the expression of numerous oncogenic genes controlling the growth and metastasis of tumor cells. The current review briefly discusses the importance of STAT3 as a potential target for cancer therapy and also provides novel insights into various classes of existing pharmacological inhibitors of this transcription factor that can be potentially developed as anti-cancer drugs.